A modified perlite protocol with a mixed dimethyl sulfoxide and trehalose cryoprotectant improves the viability of frozen cultures of ectomycorrhizal basidiomycetes. (2nd January 2019) - Sato, Masanori; Inaba, Shigeki; Sukenobe, Junji; Sasaki, Tomomi; Inoue, Ryutaro; Noguchi, Mariko; Nakagiri, Akira
ABSTRACT: Homolka's perlite protocol (HPP) was evaluated for cryopreservation of a wide range of ectomycorrhizal basidiomycete cultures, then a modified perlite protocol (MPP), in which cryoprotectant was added just before freezing rather than during the culturing process, was applied to cryosensitive strains that failed to survive when HPP was used. Further modifications of MPP with various cryoprotectants were explored to improve the cryopreservation of hard-to-preserve strains. The efficacy of HPP was assessed in 111 strains of 38 species of basidiomycetes of various cryosensitivities. After freezing strains using HPP, the viability and colony diameter of the strains were examined after 2 wk, 6 mo, and 1 y of storage at −80 C. Of the 111 strains tested, 91 survived after 1 y of storage with high viability of 80% or more, whereas the remaining 20 strains exhibited low and unstable viability. For those selected cryosensitive strains that did not survive well when HPP was used, MPP was applied with a mixture of cryoprotectants, dimethyl sulfoxide (DMSO), glycerol, and trehalose, at different concentrations and combinations. Toxicity testing of the cryoprotectants in the nonfrozen state revealed that 12% ( v / v ) glycerol was highly toxic for six strains (four species), whereas DMSO (5% and 10% [ v / v ]) was less toxic than glycerol. The viability of the cryosensitive strains after freezing demonstrated that DMSO was more efficient than glycerol, and trehalose enhanced the cryoprotective effects of both glycerol and DMSO when MPP was used for cryopreservation. Our comparative analysis of MPP with various combinations and concentrations of cryoprotectants revealed that a mixture of 5% DMSO and 10% trehalose was the most effective cryoprotectant, and that using MPP with this cryoprotectant was applicable to many cryosensitive strains.